Analisis Perbandingan Hukum Islam dan Hukum Adat dalam Implementasi Waris di Kabupaten Kolaka - Leleang, Andi Tenri; Shabnuary, Muhamamad; Yusril, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2024)
Islamic law and customary law are two legal systems that collaborate in carrying out their roles in inheritance law. This research focuses on the comparative analysis of legal dualism (Islamic law and customary law). It was found that the basic principles of Islamic inheritance law in its implementation include, proportionately determined by the heirs (who is entitled and how much), carried out after the completion of the arrangement of the body, debts and wills of the deceased, and carried out on the basis of mutual agreement among the heirs. Meanwhile, the principles of the implementation of customary inheritance law include, the important role of customary elders in the division and resolution of conflicts regarding inheritance, generally carried out in a familial manner with a concept that has usually been passed down from generation to generation in the family, and paying attention to the kinship systemThe implementation of inheritance is not only a legal obligation, but also has an impact on the representation of social and social ties, economic stability, and family prosperity. The implementation of inheritance is not only a legal obligation, but also has an impact on the representation of social ties, economic stability, and family prosperity. Therefore, it has a positive impact and a negative impact on the heirs.